Combination of Variable Loads in Structural Design - Tuomo Poutanen (Applied Sciences, 2024)
This study delves into the intricacies of variable load combination factors (ψ) within structural codes under fundamental design scenarios, with Eurocodes serving as the primary reference. Currently, variable loads are combined by adding one load, the leading load with its full value, and the other load, the accompanying load, with a reduced value multiplied by a combination factor ψ. This approach employs an independent load combination methodology, utilizing hypothetical reference materials. In contrast, this paper advocates for a shift towards dependent load combination, anchored in the use of actual reference materials. Specifically, it is proposed that imposed loads be combined without the combination factor, i.e., ψ = 1. Given that combination factors are in approximate unity or pertain to infrequent load cases, this research recommends the elimination of ψ from codes altogether. This recommendation stems from the recognition that the current combination factor calculation excels in cases with approximately equal loads with a significant reliability gain, while more frequent unequal loads introduce a minor reliability gain and harmful unsafe errors. Despite the overall minor safety advantage of about 2–3% being negligible considering unavoidable safe errors of about 7% in codes, this simplification significantly reduces code complexity, enhances user-friendliness, and substantially decreases the workload associated with design processes.